2002
DOI: 10.1038/sj.jhh.1001288
|View full text |Cite
|
Sign up to set email alerts
|

Weak effect of hypertension and other classic risk factors in the elderly who have already paid their toll

Abstract: The aim of the CASTEL, a population-based (n ‫؍‬ 3282) prospective study which began 14 years ago, was to identify those items which had a prognostic impact in the elderly, and to evaluate whether the typical cardiovascular risk factors, particularly arterial hypertension, play a role after the age of 65 years. Initial screening, final follow-up and annual detection of mortality were performed. Mantel-Hanszel approach and multivariate Cox model were used for statistics. Cardiovascular mortality was 23.3% in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 61 publications
2
28
0
2
Order By: Relevance
“…[1][2][3][4][5] However, several studies have shown that awareness of hypertension and BP control is still suboptimal, 1 and thus effective strategies should be developed to improve BP control and adherence to therapy. One of the methods used to achieve these goals is represented by self-measurement of BP at home by automatic devices.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] However, several studies have shown that awareness of hypertension and BP control is still suboptimal, 1 and thus effective strategies should be developed to improve BP control and adherence to therapy. One of the methods used to achieve these goals is represented by self-measurement of BP at home by automatic devices.…”
mentioning
confidence: 99%
“…The lack of predictive value of lipids in hypertensive patients could be related to the significantly higher proportion of patients older than 60 years of age and the respectively lesser importance of lipid abnormalities in the pathogenesis of coronary events in this age group. 23 Limitations of this study include our classification of having a history of hypertension based on whether or not the patient ever received treatment for elevated blood pressure in the past instead of using serial blood pressure measurements. Because the original study was not focused on hypertension, multiple systematic blood pressure measurements were not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the very elderly there is also an element of selection bias (a biological survivor effect) that starts to mask the impact of many conventional population risk factors (including pulse pressure) in the individual. 13 The use of regression analysis is common in population samples and the assumptions made are many. One unjustified one that we perhaps too often forget (commentators, reviewers and editors included) is that parameters that are statistically correlated in a population sample do so because of causality in the individual.…”
Section: Is It a Valid Deduction?mentioning
confidence: 99%